Determination of the Amplitude - Frequency Characteristics of the Well Pressure Preventing the Destruction of Wellbore Rocks (Global Journal of Science Frontier Research, 2020)
The article investigated the deformation processes of the well wall, adopted by the self-plastic model of volcanic rocks, and solved the problem of dynamic instability. A method has been developed to estimate the velocity and amplitude characteristics of the well pressure change that prevents the loss of stability of the mountain rocks (that is, to prevent the collapse and collapse of the well-elastic rock rocks in the wall). On the basis of the theoretical study of the relative deformation of the volume-self-elastic mountain rocks at periodic changes of the additional pressure in the spatial space, the conditions for its stationary and unstable variations are established.
Keywords: borehole; mountain rocks; face-plastic model; deformation processes; dynamic instability; frequency and amplitude characteristics; volume deformation